Relationship of swimming distance, expectancy, and performance to mood states of competitive athletes - Berger, B. G.; Grove, J. R.; Prapavessis, H.; Butki, B. D. (Perceptual and Motor Skills, 1997)
This study focused on the relationship between normal and abbreviated training sessions for young competitive swimmers and acute changes in mood. Several potential moderators of the relationship between exercise and mood also were examined. 25 girls and 23 boys, swimmers between the ages of 12 and 25 years, completed a shortened version of the Profile of Mood States before and after normal-distance and taper practices. An hypothesized interaction between distance training and acute changes in scores on Total Mood Disturbances was significant. During normal-distance practices, scores on Mood Disturbance increased from pre- to postpractice. Analyses of the individual subscales indicated that swimmers" scores increased for Fatigue and decreased for Vigor. In abbreviated practice sessions, athlete's scores on Total mood Disturbance showed no change from pre- to postpractice. The specific subscales, however, showed positive changes for Depression, Confusion, and Tension. The mood changes related to practice distance were not influenced by the possible moderating factors of expectancy or performance times. Thus, even for highly trained competitive swimmers, exercising at or near maximal physical capability is associated with few positive changes in mood scores. Shorter-distance swims that do not tax endurance are preferable, if mood enhancement is a goal.